Acarbose improved survival for Apc+/Min mice. Issue 2 (6th January 2020) - Dodds, Sherry G.; Parihar, Manish; Javors, Martin; Nie, Jia; Musi, Nicolas; Dave Sharp, Zelton; Hasty, Paul
Abstract: Acarbose blocks the digestion of complex carbohydrates, and the NIA Intervention Testing Program (ITP) found that it improved survival when fed to mice. Yet, we do not know if lifespan extension was caused by its effect on metabolism with regard to the soma or cancer suppression. Cancer caused death for 80% of ITP mice. The ITP found rapamycin, an inhibitor to the pro‐growth mTORC1 (mechanistic target of rapamycin complex 1) pathway, improved survival and it suppressed tumors in Apc +/Min mice providing a plausible rationale to ask if acarbose had a similar effect. Apc +/Min is a mouse model prone to intestinal polyposis and a mimic of familial adenomatous polyposis in people. Polyp‐associated anemia contributed to their death. To address this knowledge gap, we fed two doses of acarbose to Apc +/Min mice. Acarbose improved median survival at both doses. A cross‐sectional analysis was performed next. At both doses, ACA fed mice exhibited reduced intestinal crypt depth, weight loss despite increased food consumption and reduced postprandial blood glucose and plasma insulin, indicative of improved insulin sensitivity. Dose‐independent and dose‐dependent compensatory liver responses were observed for AMPK and mTORC1 activities, respectively. Only mice fed the high dose diet exhibited reductions in tumor number with higher hematocrits. Because low‐dose acarbose improved lifespan but failed to reduced tumors, its effects seem to be independent of cancer. These data implicate the importance of improved carbohydrate metabolism on survival. Abstract : Acarbose, a commonly used drug to treat diabetes, extends lifespan in a Apc Min/+ cancer‐prone mice